A study on food waste utilization for fertilizer production: Analysis of physical and chemical properties (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Food waste is generated daily in every household worldwide, posing significant challenges to waste management. Disposal in landfills consumes substantial land, water, and fertilizer resources while releasing methane gas that contributes to global warming. This study investigated the nutrient content and physicochemical properties of biofertilizer produced via the Bokashi composting system. Physical characterization focused on liquid fertilizer concentration and moisture content. Results showed that liquid fertilizer from the Bokashi bin had a higher concentration at outdoor temperature, although the yield was lower (0.0073 ratio) than at room temperature. Moisture content in samples at the room temperature was 99.27% higher than those stored outdoors. However, degraded film samples at outdoor temperature had a greater average weight (9 g) compared to room temperature (5 g). The fertilizer was analyzed for nitrogen (N), phosphorus (P) and potassium (K) concentrations. For chemical characterization, total nitrogen content was measured using the Kjeldahl method according to Malaysian Standard MS 417: Part 3: 1994. The results showed that the thin film fertilizer contained 0.3% nitrogen, which is higher than that of the liquid fertilizer. Phosphorus content was determined using UV-Visible Spectroscopy at 740 nm, with the liquid fertilizer at room temperature showing a higher phosphorus concentration of 4.117 mg/L. Potassium concentration in the film fertilizer was found to be 156.1 mg/L, as analyzed using Atomic Absorption Spectroscopy (AAS). These findings highlight the potential of Bokashi-based and films bio-fertilizers as a sustainable solution for nutrient recovery and food waste reduction.
Keywords: food waste; bio-fertilizer; nitrogen; potassium; phosphorus